Microwave photonic signals conversion using stimulated Brillouin scattering - Shen, Yichun; Zhang, Xianmin; Shen, Guofeng; Chen, Kangsheng (Optics communications, 2005)
A novel and simple technique for microwave photonic signal up and down conversion based on stimulated Brillouin scattering is presented. The optic-link is simplified using a fiber Bragg grating to extract Stokes wave to mix with 11 GHz microwave photonic signal for down conversion. The down converted intermediate frequency (IF) signal power can be controlled by tuning the reflectivity of fiber Bragg grating. It is also demonstrated that this technique can be used for up converting IF signal to around 11 GHz microwave. The technique for 22 GHz microwave photonic signals down conversion is also presented. It is based on second order Stokes wave resulted from stimulated Brillouin scattering in optical fiber.